The Determinants Of Capital Structure: A Study Of Jordanian Industrial Corporations - Ababneh, Khalid Salah (2008)
Thc research in the area of capital structure in the emerging markets like Jordan and Malaysia has only recently appeared. Tradition factors such as profitability, tangible assets share, the company size, taxes and growth opportunities were shown to influence the capital structure of firms. Apart from traditional factors, the researchers also revealed the influence of specific factors such as an analysis of the Hungarian companies has shown that companies whose main shareholder is the state or those in the industrial sector of the economy, have a bidder share of debt. Thus, this study provides the determinants of Jordanian Industrial firms' capital structure since Jordanian capital market is undergoing a comprehensive capital market reforming policy since 1978. Market capitalization of subscribed share is currently around JD 37.5 billion, to around JD 286 million in 1978. Listed companies rose from 66 in 1978 to 260 in 2008. The findings of this study suggest that the firm size, liquidity, profitability and growth of the Jordanian companies exert significant effect on the capital structure choice. Firm size has been found to be a factor in determining capital structure (Scott and Martin, 1976; Ferri and Jones, 1979; Booth et al., 2001). In a study of factors influencing capital structure of the company, Rajan and Zingales (1995) reported that an increased debt ratio is associated with firm size. The large firm hold more diversified portfolio and have better access to credit markets, thus able to support more debt than small firms.